2016
DOI: 10.1007/s13277-015-4747-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel NRAGE involved in the radioresistance of esophageal cancer cells

Abstract: Radiotherapy (RT) is one main method for the treatment of esophageal squamous cell carcinoma (ESCC), and the radioresistance is the predominant cause of patients with local recurrence. The previous results of gene microarray and subsequent verification showed that NRAGE might be involved in radiation resistance of ESCC cells. In this study, we reestablished human esophageal carcinoma radioresistant cell lines TE13R120 and ECA109R60 with gradient dose irradiation as previously reported, respectively. NRAGE expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Experimental analyses were conducted as described previously [11] , [23] and detailed in Supplementary materials and methods.…”
Section: Sem Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental analyses were conducted as described previously [11] , [23] and detailed in Supplementary materials and methods.…”
Section: Sem Analysismentioning
confidence: 99%
“…Our previous studies indicated that NRAGE was upregulated in ESCC radioresistant cells and extremely likely to be an RT-related critical factor [11,19,24]. Inadequately, there was lack of direct evidence to con rm the effect of NRAGE on resistancepromoting to IR.…”
Section: Overexpression Of Nrage Induces Radioresistance Of Escc Cellmentioning
confidence: 99%
See 3 more Smart Citations